Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Answer:
Step-by-step explanation:
a) fg(x)
--> f(5x)
--> 3(5x)+3
--> 15x+3
b) f+g(x)
--> 3x+3+ 5x
c) (f-g)(2)
3x+3- 5x
--> 3(2)+3-5(2)
--> -1
Answer:
solution given:
f(x) = 3x+3
g(x) = 5x
now
(f times g)(x)=?
(f+g)=?
(f-g)=?
we have
(f times g)(x)=f(g(x))
substituting value of g(x)
f(g(x))=f(5x)
now replacing value of x in f(x)
f(5x)=3(5x)+3
solving it
f(5x)=15x+3
so (f times g)(x) =15x+3
Step-by-step explanation:
again,
(f+g)(x)=f(x)+g(x)=3x+3+5x=8x+3
so
(f+g)(x) =8x+3
again
we need to find (f-g)(x) first so
(f-g)(x)=f(x)-g(x)=3x+3-5x=-2x+3
now
(f-g)(2)=-2*2+3=-1
(f-g)(2)=-1
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.